The association between intimate partner violence type and mental health in migrant women living in Spain: findings from a cross-sectional study - Bentley, Abigail; Riutort-Mayol, Gabriel (Frontiers in Public Health, 2023)
The association between intimate partner violence (IPV) and mental health has been clearly established in the literature, however the differential associations between IPV type and mental health are less well understood, particularly in migrant groups who are at increased risk of both IPV and poor mental health. Under-studied and emerging forms of violence such as economic abuse and technology-facilitated abuse must be considered alongside more traditionally studied forms of IPV in order to fully understand the complex nature of violence. This study makes a novel contribution to the literature by assessing multiple forms of IPV including psychological, physical, sexual, economic and technology-facilitated IPV and their relationship with symptoms of depression and anxiety in migrant women, disaggregated by IPV type. A cross-sectional survey of migrant women living in the Valencian Community of Spain was conducted, to assess experiences of IPV and symptoms of mental health. Regression analysis from the Bayesian perspective was performed. 1,998 women accessed the survey. They had an average age of 37, and came predominantly from Europe (49%), namely Western Europe, followed by Latin America (38%). The majority had been in Spain between one and three years, and 80% had resident status. A total of 1,156 responded to questions on violence and mental health. Results showed that the prevalence of IPV was high, with 59% of women reporting any experience of violence. Economic abuse was the most commonly reported form of violence, and showed the strongest relationship with symptoms of depression. Sexual violence was the strongest predictor of anxiety. In both cases, in the presence of violence, the odds of having more severe symptoms of depression and anxiety increases by over 2.25. Technology-facilitated abuse was as detrimental to women’s mental health as face-to-face violence. The findings from the study are relevant to researchers, policy-makers and service providers. They highlight the complex nature of IPV experiences faced by migrant women and the importance of understanding how different types of IPV can impact migrant mental health, in order to ensure survivors receive adequate care.